Management : a practical introduction - Kinicki, Angelo; Williams, Brian K., 1938- (Boston : McGraw-Hill/IRWIN, 2009)
Blending scholarship and imaginative writing, ASU business professor Kinicki (of Kreitner/Kinicki Organizational Behavior 8e) and writer Williams (of Williams/Sawyer Using Information Technology 7e and other college texts) have created a highly readable introductory management text with a truly unique student-centered layout that has been well received by todays visually oriented students. The authors present all basic management concepts and principles in bite-size chunks, 2- to 6-page sections, to optimize student learning and also emphasize the practicality of the subject matter. In addition, instructor and students are given a wealth of classroom-tested resources.
Includes indexes.
1
Keywords: Management